Effects of Xylo-Oligosaccharides on Growth and Gut Microbiota as Potential Replacements for Antibiotic in Weaning Piglets - Chen, Yuxia; Xie, Yining; Zhong, Ruqing; Liu, Lei; Lin, Changguang; Xiao, Lin; Chen, Liang; Zhang, Hongfu; Beckers, Yves; Everaert, Nadia (Frontiers in Microbiology, 2021)
Xylo-oligosaccharides (XOS) is a well-known kind of oligosaccharide and extensively applied as a prebiotic. The objective of this study was to investigate the effect of XOS supplementation substituting chlortetracycline on growth, gut morphology, gut microbiota, and hindgut short chain fatty acid contents of weaning piglets. A total of 180 weaned piglets were randomly allocated to three treatments for 28 days, as follows: control group (basal diet, CON), basal diet with 500mg/kg (XOS500) XOS, and positive control (basal diet with 100 mg/kg chlortetracycline, CTC). Compared with the CON group, the piglets in the XOS500 group improved body weight on days 28, average daily gain and reduced feed : gain ratio during days 1–28 (P < 0.05). The XOS500 supplementation increased Villus Height and Villus Height : Crypt Depth Ratio in the ileum (P <0.05). Villus Height : Crypt Depth of the ileum was also increased in the CTC treatment group (P <0.05). Meanwhile, the XOS500 supplementation increased significantly the numbers of goblet cells in the crypt of the cecum. High-throughput 16S rRNA gene sequencing revealed distinct differences in microbial compositions between the distal ileum and cecum. XOS500 supplementation significantly increased the bacterial diversity. However, CTC treatment markedly reduced the microbial diversity (P < 0.05). Meanwhile, XOS500 supplementation in the diet significantly increased the abundance of Lactobacillus genus compared to the CON and CTC group in the ileum and cecum (P < 0.01), whereas the level of Clostridium_sensu_stricto_1, Escherichia-Shigella and Terrisporobacter genus in the XOS500 group were markedly lower than the CON and CTC group (P < 0.05). In addition, dietary supplementation with XOS500 significantly increased the total short-chain fatty acids, propionate and butyrate concentrations and decreased the acetate concentration compared to the CON group in the cecum (P < 0.05). In summary, dietary supplemented with XOS500 could enhance specific beneficial microbiota abundance and decrease harmful microbiota abundance to maintain the structure of the intestinal morphology and improve growth performance of weaned piglets. Thus, XOS may potentially function as an alternative to feed-grade antibiotics in weaned piglets during modern husbandry.